Let a,b,c be three variables. Then the followings are some basic rules of algebra applicable to these variables.

**In the next section**,

we make use of these simple formulas to find solutions to given problems.

Using the Commutative Law for Addition stated above

`a + b = b + a`

=> For the given expression, x = 5

Using of the Commutative Law For Multiplication stated above

` a . b = b . a`

=> For the given expression, r = 2

According to the Distributive Law, we have

`a . ( b + c ) = ( a . b ) + ( a . c )`

Through comparison of the given expression with the above formula, we conclude that

m = a = 2

We can also prove that m = 2 by method of equating the two sides of the given expression as shown below.

Given that

2 . ( 3 + 1 ) = ( 2 . 3 ) + ( m . 1 )

L.H.S (Left Hand Side) = 2 . ( 3 + 1 )

= 2 . 4 = 8

R.H.S (Right Hand Side) = ( 2 . 3 ) + ( m . 1 )

= 6 + m

By equating the two sides,

8 = 6 + m

=> m = 2 (Subtract 6 from both sides of the equation)

Hence we get the same answer as we got using the Distributive Formula.

Here we make use of the Associative Law For Multiplication which states that for any variables a, b and c

`a . ( b . c ) = ( a . b ) . c`

Through comparison we get

d = c = 5

Using the Cancellation law For Addition

`a + c = b + c iff a = b `

Here a = x, b = 5, c = 2

And the formula states that the identity will hold if and only if a = b i.e., if x = 5

Using the Cancellation law For Multiplication

`a . c = b . c iff a = b ` where c != 0

Here

a = n

b = 5

c = 3 != 0

Hence the equation will hold if and only if a = b, that is if n = 5

We have studied Distributive law which states that

`a . ( b + c ) = ( a . b ) + ( a . c )`

Here we can split up 14 = 10 + 4

=> 4 . ( 10 + 4 ) = ( 4 . 10 ) + ( 4 . 4 )

=> 4 x 14 = 40 + 16 = 56

Hence we can split our problem using this property and find the solution with greater ease.

We have studied that in the distributive property, we distribute the operation of multiplication over addition. We can use this property to simplify the above expression.

We see that both 3, and 9 are multiples of 3. So if we take 3 out of the above expression, leaving the rest inside the parentheses, what we get is a distributed equivalent of the above expression.

=> 3x + 9 = 3 ( x + 3 )

A mentionable point here is that the property also holds for subtraction. For example

=>` 3x-9 = 3(x-3 )=3 ( x+(-3 ) )`

Using the Associative Property for Multiplication

` a . ( b . c ) = ( a . b ) . c`

=> 2 x ( 4 x n ) = ( 2 x 4 ) x n

=> 2 x ( 4 x n ) = 8 x n

Here we need to mention that subtraction, division, matrix multiplication, vector product are all non-commutative.

`4-2!=2-4` => Subtraction is non-commutative

`( 4 )/( 2 )!=2/( 4 )` => Division is non-commutative

Similarly Matrix Multiplication and vector Product can be shown to be non-commutative.

© 2014 iPracticeMath | All Rights Reserved | Terms of Use.